Nursing care to elderly in the Intensive Care Unit - Juliana Mendes; Mariluci Alves Maftum; Maria Ribeiro Lacerda; Maria de Fátima Mantovani; Rosalina Aparecida Partezani Rodrigues (Universidade Federal Fluminense, Escola de Enfermagem Aurora de Afonso Costa, 2009)
Qualitative and exploratory research, developed in a Semi-Intensive Care Unit (SICT), on a Public Teaching Hospital in Curitiba, Paraná, in 2008. The objective is to know how the nurses perceive the nursing care to the elderly hospitalized in the SICT. Seven nurses which work in the SICT participated the research. Data were collected through semi-structured interview and they were treated with the technique of thematic analysis. Three categories were unveiled: Elderly singularities affecting nursing care, nurse's perceptions on the care delivered to the elderly; nurse's preparation for caring of the elderly. For the research subjects, changing on the profile of the SICT clients, there's a need to deliver a differentiated care, because of the increasing number of elderly in this Units, and due of the singularities of this specific phase of the life cycle, as well as their vulnerability to chronic and transmissible diseases, and complications during treatments. They stated that they face some difficulties on caring because of the lack of knowledge on Gerontology Nursing. So, there's evidence that nursing professionals should know about elderly issues, as well as about the public policies to deliver the gerontological care.